PENGARUH KEPUTUSAN FINANSIAL, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Ni Ayu Nesa Laksmini; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2020)
The companyis goal is to maximize thei companyis wealth or value for shareholders. Maximizingi thi value of the company is very important, meaningi that increasingi the value of the company also means increasingi the prosperity of thei shareholders which is thei companyis main goal. This study examines thei effect of investment decisions, fundingi decisions, dividenid policy, profitability and company growth on firm value. The number of samples in this study were 20 companies. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that investment decisions, dividenid policy and profitability have a positive and significant effect on firm value. While company growth has a negative and significant effect on firm value, and fundingi decisions have no significant effect on firm value